Application of response surface methodology (RSM) for process analysis and optimization of milk processing wastewater treatment using multistage flexible fiber biofilm reactor. Issue 3 (June 2020) - Abdulgader, Mohamed; Yu, Qiming Jimmy; Zinatizadeh, Ali Akbar; Williams, Philip; Rahimi, Zahra
Abstract: In this work, a multistage flexible fibre biofilm reactor (MS-FFBR) composed of four equal-size compartments was used successfully to treat milk processing wastewater (MPW). Response surface methodology (RSM) was also used to evaluate, model, and optimize the performance of the MS-FFBR. The effect of variation of two process variables (CODin and HRT) on the system performance was evaluated by measuring different responses (TCOD, SCOD, TBOD5, SBOD5, TSS removal efficiency, turbidity, pH, SRT and U). From findings, the maximum removal efficiency in terms of TCOD, SCOD, TBOD and SBOD was achieved at 12 h HRT and 1590 mg L −1 CODin, whereas the lowest removal efficiencies were observed at 8 h HRT and 5869 CODin. The minimum TSS removal efficiency was obtained at 8 h HRT and 3750 mg L −1 . More importantly, the MS-FFBR indicated good buffering capacity throughout the experiments. The optimum region was found at HRT less than 8 h and 1500 mg L −1 < CODin < 2635 mg L −1 . The experimental findings were in close agreement with the model prediction.